(untitled) (Journal of Economic Research & Business Administration, 2018)
The article explores the formation of a favorable economic environment for the development of industrial and innovation infrastructure. As its main components are determined: legislative and legal support for economic initiatives, creation of equal conditions for participants in the innovation process, deepening public-private partnership in the implementation of innovative projects, introducing tools to stimulate the interrelation between science and production, encouraging the identification of non-state sources of funding, granting tax breaks and vacations, support and development of venture business. The authors of the article argue that the creation of a favorable economic environment contributes to the creation of new innovation-diversified, as well as the development of existing elements of the industrialinnovative infrastructure, including technology parks, technological business incubators, and non-state innovation funds.